Fundamental questions in cross-cultural psychology - Vijver, Fonds J. R. van de; Chasiotis, Athanasios; Breugelmans, Seger M. (Cambridge, [England] Cambridge University Press, 2011)
"Cross-cultural psychology has come of age as a scientific discipline, but how has it developed? The field has moved from exploratory studies, in which researchers were mainly interested in finding differences in psychological functioning without any clear expectation, to detailed hypothesis tests of theories of cross-cultural differences. This book takes stock of the large number of empirical studies conducted over the last decades to evaluate the current state of the field. Specialists from various domains provide an overview of their area, linking it to the fundamental questions of cross-cultural psychology such as how individuals and their cultures are linked, how the link evolves during development, and what the methodological challenges of the field are. This book will appeal to academic researchers and postgraduates interested in cross-cultural research"--Provided by publisher.
Introduction / Fons J.R. van de Vijver, Athanasios Chasiotis and Seger M. Breugelmans -- Part 1. Setting the Stage: 1. Fundamental questions of cross-cultural psychology / Fons J.R. van de Vijver, Athanasios Chasiotis and Seger M. Breugelmans -- Part 2. Explanation of Cross-Cultural Differences: 2. Past and present of cross-cultural psychology / Gustav Jahoda; 3. The continuing challenge of discovering psychological 'order' across cultures / Walt J. Lonner; 4. The ecocultural framework: a stocktaking / John W. Berry; 5. Frameworks for explaining cross-cultural variance: a meta-analytic examination of their usefulness / Dianne A. van Hemert; 6. The relationship between individual and culture / Seger M. Breugelmans -- Part 3. Methods to Study Culture: 7. A fourfold conceptual framework for cultural and cross-cultural psychology: relativism, construct universalism, repertoire universalism, and absolutism / Johnny R.J. Fontaine; 8. About chicken and eggs: four methods for investigating culture-behaviour links / Ronald Fischer; 9. Qualitative and mixed methods research in cross-cultural psychology / Alison Karasz; 10. Bias and real differences in cross-cultural differences: neither friends nor foes / Fons J.R. van de Vijver -- Part 4. The Role of Development: 11. Cross-cultural research in the cultural historical activity theory tradition / Michael Cole, Boris G. Meshcheryakov and I.V. Ponomariov; 12. Self, family, and culture: what is common, what changes? / Çiğdem Kağitçibaşi; 13. Biology, culture, and development: conceptual and methodological considerations / Heidi Keller; 14. Differences and universals in families across cultures / James Georgas; 15. An epigenetic view on culture: what evolutionary developmental psychology has to offer for cross-cultural psychology / Athanasios Chasiotis -- Part 5. Concepts of Culture: 16. Cross-cultural differences as meaning systems / Lutz H. Eckensberger; 17. Ulysses returns: lessons from the logbook of a cross-cultural wayfarer / Michael Harris Bond; 18. Values: cultural and individual / Shalom H. Schwartz; 19. The cultural contexts of organisational behaviour / Peter B. Smith; 20. Rethinking culture and the self: some basic principles and their implications / Chi-yue Chiu and Young-hoon Kim -- Part 6. Conclusion: 21. Research on behavior-and-culture: current ideas and future projections / Ype H. Poortinga.
Keywords: Ethnopsychology